Localizing the position of the Segond fracture bed under CT measurements to determine the functional tibial insertion of an anterolateral ligament - Guo, Ziteng; Wang, Xuyang; Liu, Guoshuai; Lu, Yang; Bai, Yuxi; Lv, Jian; Liu, Fei (Frontiers in Surgery, 2023)
Background Many studies have confirmed the existence of ligament structures in the anterolateral region of the knee that maintain rotational stability of the knee joint, namely, the anterolateral ligament (ALL). Most scholars believe that knee joint reconstruction should be considered during revision surgery and a high level of pivot displacement test (stage 2 or 3). During ALL reconstruction, the choice of ligament reconstruction sites affects the success rate and prognosis of the operation. Therefore, the choice of ligament reconstruction sites is particularly important. There is little research on the lateral ALL tibia insertion point, and most clinicians use the midpoint Gerdy's tubercle and fibular head as insertion points. However, the reconstruction effect is not ideal. Objective This study aims to measure the position of the Segond fracture bed on CT images to determine the ALL position of the tibia. Method To determine the position of the Segond fracture bone bed, the CT AM Volume Share 2 system was used to manually measure the position of bone fragments in 23 Segond fracture patients. Using the highest point of Gerdy's tubercle in the CT axial slices and the outermost point of the fibular head in the CT axial slices as reference points, the direction and angle of the CT slices were adjusted to ensure that the highest point of the Gerdy tubercle, the outermost point of the fibular head, and the center of Segond fracture bed were in the same sagittal slice. A CT sagittal slice measures the vertical distance from the center of the Segond fracture bed to the Gerdy-fibular line segment (G-F line segment), which is the line connecting the highest point of the segment to the outermost point of the fibula. The distance from the vertical point at the center of the Segond fracture bed of the G-F line to the highest point of the Gerdy tubercle was measured. All measurements were performed using the same measurement standard and were expressed as a percentage of the length of the G-F line. The measured results were statistically analyzed using SPSS 25.0 descriptive statistical research methods. Results The average length of the G-F segment measured on CT images was 39.6 ± 2.0 mm, and the average vertical length from the center of the Segond fracture bed to the G-F segment was 13.1 ± 1.1 mm, accounting for 33.2% ± 2.1% of the length of the G-F segment. The length from the vertical point of the fracture bed on the G-F line segment to the highest point of the Gerdy tubercle was 14.7 ± 1.3 mm, accounting for 37.1% ± 2.9% of the length of the G-F segment. Conclusion Through the study of the CT measurement of the Segond fracture location, we obtained the location of the functional tibial insertion of ALL, which is different from the anatomical insertion of ALL and is more inclined to the Gerdy tubercle and above, which has reference value for the treatment of recovering the function of anterolateral ligament after reconstruction.